First Initial community-acquired meningitis due to extended-spectrum beta-lactamase producing Escherichia coli complicated with multiple aortic mycotic aneurysms - Weyrich Pierre; Ettahar Nicolas; Legout Laurence; Meybeck Agnes; Leroy Olivier; Senneville Eric (BMC, 2012)
Abstract We report the first case of extended-spectrum beta-lactamase producing E. coli community-acquired meningitis complicated with multiple aortic mycotic aneurysms. Because of the acute aneurysm expansion with possible impending rupture on 2 abdominal CT scan, the patient underwent prompt vascular surgery and broad spectrum antibiotic therapy but he died of a hemorrhagic shock. Extended-spectrum beta-lactamase producing E. coli was identified from both blood and cerebrospinal fluid culture before vascular treatment. The present case report does not however change the guidelines of Gram negative bacteria meningitis in adults.